Repair from a chair: Computer repair as an untrusted cloud service - Ingram, Lon; Popov, Ivaylo; Setty, Srinath; Walfish, Michael (Workshop on Hot Topics in Operating Systems (HotOS), 2011)
Today, when people need their computers repaired, their process is not very different from hiring someone to fix a television: they either bring the computer to a repair service [1, 3], or they call a technician (or family member) and ask for a house call. This process is inconvenient. It also risks the privacy of customers’ data and the integrity of their systems: repair services have gained notoriety for stealing personal data from customers [22] or otherwise intruding on their privacy [7].